Fostering roles and adopting identities: exploring the effect of drama therapy on the sense of identity of Muslim orphaned and vulnerable adolescents - Shaik Omar, Naadiya (My University, 2016)
Parent mortality in South Africa is increasing, resulting in the rise of orphaned children. There is a lack of intervention and psychological support available to orphans in South Africa. Furthermore, there has been no research conducted in the field of drama therapy and its use in South Africa with Muslim adolescent orphans and identity. The research study investigates the relevance and efficacy of drama-therapeutic methodologies in the formation of communal identity and self-concept among Muslim adolescent orphans in South Africa. The study involves eight adolescent orphan participants that underwent a series of three drama therapy group sessions focused on identity. Using thematic content analysis the study found that the participants were able to use role as a therapeutic measure and to strengthen their Muslim identities. The drama therapy methodologies empowered participants and enabled them to think about themselves and their behaviour in a different way. It further enabled unconscious material to surface to the conscious mind, thereby evoking introspection and reflection. These are steps towards transformation and the conception of ultimate self that the participants have defined for themselves. This study also has implications for the adoption and adaption of drama therapy methodology in South Africa.